2013
DOI: 10.1097/wnr.0b013e32836384db
|View full text |Cite
|
Sign up to set email alerts
|

Systematic correlation between spine plasticity and the anxiety/depression-like phenotype induced by corticosterone in mice

Abstract: Unraveling the pathophysiological basis for the development of and recovery from depression is a unique challenge. Dendritic plasticity has been reported to be involved in the development of depression. We modeled an anxiety/depression-like phenotype by chronic corticosterone exposure in mice and reversed this anxiety/depression-like phenotype by long-term treatment with fluoxetine (FLX). Spine density in the hippocampus was detected by Golgi-Cox staining at five time points. The data showed that 35 days of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Interestingly, corticosterone can cause synaptic degeneration and exert toxic effects on hippocampal neurons, and finally induces depression [14]. It is also well-known that corticosterone exposure induces a decrease in dendritic spine density in hippocampus, which might be one of the pathophysiological mechanisms underlying depression progression [15]. These studies have confirmed that corticosterone is closely related to depression.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, corticosterone can cause synaptic degeneration and exert toxic effects on hippocampal neurons, and finally induces depression [14]. It is also well-known that corticosterone exposure induces a decrease in dendritic spine density in hippocampus, which might be one of the pathophysiological mechanisms underlying depression progression [15]. These studies have confirmed that corticosterone is closely related to depression.…”
Section: Introductionmentioning
confidence: 69%
“…Taken together, our data demonstrated the protective role of H 2 S against the neurotoxicity of corticosterone. It was reported that the neurotoxicity of corticosterone plays an important role in the development of depression [14,15]. In addition, our recent studies have shown that H 2 S has antidepressant-like effect [25,26].…”
Section: Discussionmentioning
confidence: 93%
“…Decreased spine densities in CA1 neurons has been associated with depression-like behaviors in a light-induced depression model, in the absence of spine changes in CA3 or dendritic changes in CA3 or CA1 [4]. Chronic corticosterone administration, which results in a depressive phenotype, reduces spine density in CA1 and both the spine and behavioral deficits recover with chronic fluoxetine administration [35, 116]. These changes occurred mainly in thin and stubby spines [116].…”
Section: Chronic Stress Alters the Number And Function Of Spine Synapsesmentioning
confidence: 99%
“…Chronic corticosterone administration, which results in a depressive phenotype, reduces spine density in CA1 and both the spine and behavioral deficits recover with chronic fluoxetine administration [35, 116]. These changes occurred mainly in thin and stubby spines [116]. Given the differential incidence of depression in women it is notable that spine morphologic changes in response to CRS are opposite in male and female rats [103].…”
Section: Chronic Stress Alters the Number And Function Of Spine Synapsesmentioning
confidence: 99%
“…Changes in spine density in CA1 have been reported to be correlated with stress exposure (Shors et al, 2001; Pawlak et al, 2005; Donohue et al, 2006), learning and memory (Moser et al, 1994, 1997), and anti-depressant effects (Wang et al, 2013) in rodents. Moreover, given that activity-regulated genes are implied to contribute to plasticity (Leslie and Nedivi, 2011), and the recent suggestions that NgRs are regulated by various forms of activity stimuli (Guo et al, 2013; Karlsson et al, 2013), we next examined whether the alterations in spine distribution seen in NgR2 −/− mice may also affect behavioral tasks in the adult, such as learning and memory.…”
Section: Resultsmentioning
confidence: 99%